PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL SMART BOOK BERBANTUAN APLIKASI CANVA PADA PEMBELAJARAN MATEMATIKA KELAS IV SDN 4 PULAU RIMAU - Gustin, Ayu; Disurya, Ramanata; Tanzimah, Tanzimah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT This study was motivated by the low learning interest of students during classroom activities, which was attributed to the use of unengaging instructional media. Therefore, the researcher took the initiative to develop a more engaging learning medium, namely the Digital Smart Book, for teaching mathematics to fourth-grade students at SD Negeri 4 Pulau Rimau. The main objective of this research was to produce a Digital Smart Book learning media that is highly valid, practical, and effective. This research falls under the category of research and development (R&D) using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results indicated that the Digital Smart Book underwent validation testing by experts in media, subject content, and language, with a score of 85.2%, which is categorized as